2014
DOI: 10.1093/eurheartj/ehu029
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted thrombolysis for acute pulmonary embolism: a systematic review

Abstract: Pulmonary embolism remains a common and potentially life-threatening disease. For patients with intermediate- and high-risk pulmonary embolism, catheter-based revascularization therapy has emerged as potential alternative to systemic thrombolysis or surgical embolectomy. Ultrasound-assisted catheter-directed thrombolysis is a contemporary catheter-based technique and is the focus of the present review. Ultrasound-assisted catheter-directed thrombolysis is more effective in reversing right ventricular dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 36 publications
1
77
0
7
Order By: Relevance
“…10 A further development is ultrasound-assisted catheter-directed thrombolysis (USAT), combining CDT with a catheter system that uses high-frequency, low-power ultrasound. 11 According to in vitro studies, ultrasound causes reversible disaggregation of uncrosslinked fibrin fibers, and ultrasound pressure waves increase thrombus penetration of thrombolytic drugs by acoustic streaming. [12][13][14] It remains controversial whether USAT is superior to conventional CDT.…”
mentioning
confidence: 99%
“…10 A further development is ultrasound-assisted catheter-directed thrombolysis (USAT), combining CDT with a catheter system that uses high-frequency, low-power ultrasound. 11 According to in vitro studies, ultrasound causes reversible disaggregation of uncrosslinked fibrin fibers, and ultrasound pressure waves increase thrombus penetration of thrombolytic drugs by acoustic streaming. [12][13][14] It remains controversial whether USAT is superior to conventional CDT.…”
mentioning
confidence: 99%
“…[2] In high-risk patients who are ineligible to receive thrombolytic therapy or whose critical status does not allow sufficient time for systemic therapy to be effective, the use of interventional catheterization techniques which are safer than systemic thrombolysis should be considered. [5] In a case report, Ozker et al [6] reported catheter thrombectomy and aspiration of massive PE in a patient with recent CABG procedure with rapid recovery of clinical status. Ultrasoundassisted catheter directed thrombolysis combines catheter-directed thrombolysis with a specific catheter which uses high-frequency, low-power ultrasound, offering rapid revascularization without increased complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasoundassisted catheter directed thrombolysis combines catheter-directed thrombolysis with a specific catheter which uses high-frequency, low-power ultrasound, offering rapid revascularization without increased complication rates. [5] There are few publications focusing on the utilization of the USAT in high-risk PE patients. Kennedy et al [7] reported 98% complete or near complete clearance of the thrombi among 60 patients with acute PE who were treated with anticoagulation and USAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Если антикоагулянтная монотерапия гепарином в первые 24-48 ч недостаточно влияет на размеры ПЖ и его функцию [304], то степень раннего восста новления ПЖ после катетерного тромболизиса низ кими дозами препаратов сравнима с эффектом си стемного тромболизиса стандартными дозами [303,335]. В рандомизированном контролируемом клини ческом исследовании (n = 59) у больных с умеренным риском при катетерном тромболизисе (введение 10 мг tPA в течение 15 ч в пораженное легкое) с ультразву ковым контролем по сравнению с монотерапией ге парином значительно уменьшалось соотношение подклапанных размеров ПЖ / ЛЖ через 24 ч от нача ла лечения без увеличения риска кровотечений [336].…”
Section: чрескожная катетерная терапияunclassified